Cauchy series in Euler number

Calculus Level 3

lim n n ( ( 1 + 1 n + 1 ) n + 1 ( 1 + 1 n ) n ) = ? \large \displaystyle \lim_{n\rightarrow\infty} \sqrt{n} \left( \left( 1+\dfrac{1}{n+1} \right)^{n+1} - \left( 1+\dfrac{1}{n} \right)^{n} \right) = \, ?


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kalpok Guha
Jun 4, 2017

Computing the limit separately first we take lim n ( 1 + 1 n + 1 ) n + 1 \lim_{n\rightarrow\infty} ( 1+\frac{1}{n+1} )^{n+1}

= e ( lim n ( 1 + 1 n + 1 1 ) ( n + 1 ) =e^(\lim_{n\rightarrow\infty} ( 1+\frac{1}{n+1} -1)(n+1) [As it is in the form 1 1^\infty ]

= e ( lim n ( 1 n + 1 ) ( n + 1 ) ) =e^(\lim_{n\rightarrow\infty} ( \frac{1}{n+1} )(n+1))

= e =e

Now

lim n ( 1 + 1 n ) n \lim_{n\rightarrow\infty} ( 1+\frac{1}{n} )^n

= e ( lim n ( 1 + 1 n 1 ) n =e^(\lim_{n\rightarrow\infty} ( 1+\frac{1}{n} -1)n [As it is in the form 1 1^\infty ]

= e ( lim n ( 1 n ) n ) =e^(\lim_{n\rightarrow\infty} ( \frac{1}{n} )n)

= e =e

Now

lim n n ( ( 1 + 1 n + 1 ) n + 1 ( 1 + 1 n ) n ) \lim_{n\rightarrow\infty} \sqrt{n} \left( \left( 1+\dfrac{1}{n+1} \right)^{n+1} - \left( 1+\dfrac{1}{n} \right)^{n} \right)

= lim n n lim n ( ( 1 + 1 n + 1 ) n + 1 ( 1 + 1 n ) n ) =\lim_{n\rightarrow\infty} \sqrt{n}*\lim_{n\rightarrow\infty} (( 1+\frac{1}{n+1} )^{n+1}-( 1+\frac{1}{n} )^n)

= lim n n ( e e ) = \lim_{n\rightarrow\infty} \sqrt{n}(e-e) [Using computed limits]

0 \boxed{0}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...